A giant ovarian mucinous cystadenoma in an adolescent: a case report - Ozgun, Mahmut Tuncay; Turkyilmaz, Cagdas (Archives of Medical Science, 2009)
Mucinous cystadenomas are rarely encountered in adolescent patients and can reach an enormous size. A 19-year-old woman was admitted to our clinic complaining about abdominal distension during the last four months. Physical examination revealed an immobile pelvic mass, which filled the whole abdomen and extended up to the processus xiphoideus. Tumour markers were within normal limits. The patient underwent right salpingo-oophorectomy via laparotomy. Mucinous cystadenoma was detected with histological examination. If the pure cystic mass reaches an enormous size and the tumour markers are within normal limits, mucinous cystadenomas should be considered in the differential diagnosis in adolescent patients.